Passage survival of European and American eels at Francis and propeller turbines - Paul G. Heisey; Dilip Mathur; Joanne L. Phipps; Jerry Christopher Avalos; Cory E. Hoffman; Steven W. Adams; Eric De‐Oliveira (Journal of Fish Biology, 2019)
We present the magnitude of losses of European eel Anguilla anguilla and American eel A. rostrata in passage through propeller and Francis turbines at hydroelectric projects. Survival and injury rates and types were turbine type related. Overall, eel survival was higher (mean ± 90% CI = 95.1 ± 5.3%,) and injury rate lower (12.5 ± 10.5) at Francis than propeller turbines (survival = 80.7 ± 6.4%; injury rate = 25.7 ± 7.9%). The common injury type at Francis turbines was bruises and at propeller turbines was severance. Blade shape and thickness of the leading edge of the blades (rounded, thick buckets of Francis turbines v . flatter, sharper edged blades in propeller turbines); eel entry routes into the turbines; their flexible, cylindrical body shape and orientation probably contributed to these differences. Relationship between survival and injury and turbine characteristics was turbine specific. For Francis turbines, one negative correlation ( r = −0.986, P r = 0.740, P r = 0.835, P

Experimental investigation of performance and emissions of a VCR diesel engine fuelled with n-butanol diesel blends under varying engine parameters - Ashish Nayyar; Dilip Sharma; Shyam Lal Soni; Alok Mathur (Environmental Science and Pollution Research, 2017)